تأثير برنامج تأهيلي وقائي للإصابة التواء الكاحل لدى ناشئين كرة القدم - إسماعيل، محمد سعد; محمد، نادر إبراهيم; إبراهيم، محمود السيد (جامعة بنها - كلية التربية الرياضية للبنين, 2021)
يهدف البحث إلى: التعرف على تصميم برنامج تأهيلي وقائي على تقليل إصابات التواء الكاحل لدى ناشئ كرة القدم - القوة العضلية للعضلات العاملة على مفصل الكاحل. - المدى الحركي للعضلات العاملة على مفصل الكاحل. فروض البحث: تحقيقا لأهداف البحث وضع الباحث الفروض التالية: - توجد فروق دالة إحصائيا ومعدل تغير حادث بين القياسين القبلي والبعدي لناشئي كرة القدم في المتغيرات البدنية لصالح القياس البعدي. - توجد فروق دالة إحصائيا ومعدل تغير حادث بين القياسين القبلي والبعدي لناشئي كرة القدم في متغيرات تقليل إصابة الكاحل لصالح القياس البعدي. المنهج المستخدم: استخدم المنهج التجريبي باستخدام التصميم التجريبي. عينة البحث: قام الباحث باختيار عينة البحث بالطريقة العمدية من ناشئ كرة القدم من نادى الإنتاج الحربي الرياضي بمحافظة القاهرة والبالغ عددهم (١٥) ناشئ، قام الباحث بتطبيق دارسة استطلاعية على عدد (٥) ناشئين كرة قدم من خارج عينة البحث لحساب المعاملات العلمية للاختبارات المستخدمة في الدراسة. وقد قام الباحث بإجراء قياسات البحث القبلية والبعدية على عدد (١٠) ناشئين والمنتظمين في تطبيق التجربة الأساسية للدراسة. الاستخلاصات: في ضوء هدف البحث وما توصل إليه الباحث من الأسلوب الإحصائي المستخدم وما أسفرت عنه الدراسة من الفروق والعلاقات استخلص الباحث الاستخلاصات التالية: 1. أدى البرنامج التأهيلي الوقائي إلى تحسن مستوى الكفاءة البدنية لدى ناشئ كرة القدم بنادي الإنتاج الحربي. ٢. هناك علاقة إيجابية بين البرنامج التأهيلي الوقائي وتقليل إصابة التواء الكاحل لدى ناشئ كرة القدم بنادي الإنتاج الحربي. ٣. أنه توجد فروق جوهرية ذات دلالة إحصائية عند مستوى (٠.٠١) بين متوسطي القياسين القبلي والبعدي لدى ناشئي كرة القدم في المتغيرات البدنية قيد البحث، وذلك لصالح متوسط درجات القياس البعدي. ٤. أن هناك معدل تغير حادث بين متوسطي القياسين القبلي والبعدي لدى ناشئي كرة القدم في المتغيرات البدنية قيد البحث، وكان أكبر معدل تغير حادث في متغير الاتزان الثابت (الوقوف على مشط القدم) بنسبة مئوية.
The research aims to Identify the design of a preventive rehabilitation program to reduce sprained ankle injuries among young footballers and know its impact on: - Muscular strength of the muscles working on the ankle joint. - The range of motion of the muscles operating on the ankle joint. Research hypotheses: To achieve the objectives of the research, the researcher put the following hypotheses: - There are statistically significant differences and the rate of change of an accident between the pre and post measurements of beginners soccer in the physical variables in favor of the post measurement. - There are statistically significant differences and the rate of change of accident between the pre and post measurements of junior soccer in the variables of reducing ankle injury in favor of post measurement.. Used approach: He used the experimental method using the experimental design. Research sample: The researcher selected the research sample by the deliberate method from the football junior from the Military Production Club in Cairo Governorate, whose number is (15) youth. The researcher applied an exploratory study on a number (5) footballers from outside the research sample to calculate the scientific parameters of the tests used in the study. The researcher conducted pre and post measurements on a number of (10) students who were regular in applying the basic experience of the study. Conclusions: In light of the aim of the research and the researcher's findings of the statistical method used, and the differences and relationships that the study resulted in, the researcher drew the following conclusions: 1- The preventive rehabilitation program led to an improvement in the level of physical competence of the football youth in the Military Production Club. 2- There is a positive relationship between the preventive rehabilitation program and the reduction of ankle sprain injury among the football junior at El Entag El Harby Club. 3- That there are substantial differences of statistical significance at the level (0.01) between the averages of the pre and post measurements among the beginners of football in the physical variables under study, in favor of the average scores for the post-measurement. 4- That there is an accident change rate between the averages of the pre and post measurements among the beginners of football in the physical variables under discussion, and the largest accident change rate was in.
Keywords: البرامج الوقائية -- التأهيل الرياضي -- الإصابات الرياضية -- كرة القدم